The power of social and political networking for recruitment and promotion for strategic positions: a Gender perspective on work relations at workplaces - Hossain, Dewan Mahboob; Rokis, Rohaiza (Canadian Center of Science and Education, 2015)
Gender issues at the workplaces receive immense importance from the researchers all over the world. This study emphasizes on the core questions: how men and women maintain networks in the organizations and whether their networking strategies are different from each other. Most of the studies on this issue conducted so far are mainly based on the developed economic-based nations. This particular study however looks into this issue in the context of a developing economy of Bangladesh. By taking an old, well-reputed and large public University as a case, this study concludes that men and women have different networking strategies. Women’s networks mainly revolve around women. Moreover, women are not that much interested in establishing and maintaining networks like men in the workplaces. Rather, women remain more concerned with their family affairs. These situations apparently do not directly beneficial to women on a whole. Working women are deprived from recruitment, promotion and obtaining strategic positions at the workplaces. Men, on the other hand, due to their solid and significant social networking manage to maintain positive working avenues and therefore secure their positions further